Bentuk Penyajian dan Fungsi Musik Jonggan di Desa Bebatung Kecamatan Mandor Kabupaten Landak - Ranto M, M Aristo; Muniir, Asfar (Universitas Tanjungpura, 2022)
This research is motivated by the lack of written documentation so that references to the Form of Presentation and Function of Jonggan Music in Bebatung Village, Mandor District, Landak Regency need to be researched. The purpose of this study is to describe the form of presentation of Jonggan music in Bebatung village, Mandor district, Landak district and to describe the function of Jonggan music in Bebatung village, Mandor district, Landak district. The method in this research is descriptive method with the form of qualitative research and ethnomusicological approach. Data collection techniques in the form of observation, interviews and documentation studies. The technique of testing the validity of the data used is the extension of observations and triangulation of sources. Based on data analysis, it can be concluded that the form of presentation and function of Jonggan's music in Bebatung Village, Mandor District, Landak Regency is traditional music with the form of presenting music being played together or in an ensemble. The players consist of one Agukng (Gong) player, two Dau (Kenong) players, one Tuma (Ketubung) player and one Solekng (Flute) player. The function of Jonggan Music in Bebatung Village, Mandor District, Landak Regency has a function as (1) As accompaniment music, (2) entertainment facilities, (3) as social facilities (4) as economic facilities (5) as a means of communication (6) as a means of education.